ANALISIS PENERAPAN KRITERIA MALCOLM BALDRIGE (MBCfPE) TERHADAP KUALITAS KINERJA DI KSPPS BMT DAS PURBALINGGA - Dwi Retno Ardani; Hawin Mu’alif Maulana; Nabila Khairunnisa Azhar; Yoiz Shofwa Shafrani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the implementation of the Malcolm Baldrige Criteria for Performance Excellence (MBCfPE) in enhancing performance quality at KSPPS BMT DAS Purbalingga, a sharia microfinance institution in Indonesia. Using a descriptive quantitative approach, the study assesses seven dimensions of MBCfPE—Leadership, Strategic Planning, Customer Focus, Measurement, Knowledge Management, Workforce Focus, Process Management, and Results. The findings reveal that BMT DAS Purbalingga achieved an overall score of 830, categorizing it as a